2020
DOI: 10.3389/fmicb.2020.01412
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Listeria monocytogenes Isolated From Ready-to-Eat Meat and Meat Processing Environments in Poland

Abstract: Listeria monocytogenes is one of the major foodborne pathogens. Isolates of PCRserogroups IIb (n = 17) and IVb (n = 31) recovered from food (n = 33) and food processing environment (n = 15) in Poland were characterized using whole genome sequencing. Most isolates belonged to Multi-Locus Sequence Type (MLST) ST2 (31.3%) and ST5 (22.9%). Core genome MLST (cgMLST) analysis classified isolates into seven sublineages (SL) and 25 different cgMLST types (CT). Consistent with the MLST results, most sublineages were SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 43 publications
7
38
2
Order By: Relevance
“…Additionally, 11 strains (IDs: 47080, 47081, 47082, 47083, 47105, 47106, 47111, 47113, 47115, 47119, 47120) from the current study, classified to SL2-ST145-CT375 and mainly recovered from raw meat (10 strains) were identical, based on the cgMLST allelic profile, with strains with ID 27850 and ID 27852 from RTE food previously described in Poland [ 40 ]. Similarly, such a close molecular relatedness was also observed among 10 strains classified to SL2-ST2-CT4325, isolated mainly from RTE food and four strains (IDs: 27816, 27834, 27838, 27842) characterized by Kurpas et al [ 40 ] ( Figure 3 , Tables S1 and S3 ).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Additionally, 11 strains (IDs: 47080, 47081, 47082, 47083, 47105, 47106, 47111, 47113, 47115, 47119, 47120) from the current study, classified to SL2-ST145-CT375 and mainly recovered from raw meat (10 strains) were identical, based on the cgMLST allelic profile, with strains with ID 27850 and ID 27852 from RTE food previously described in Poland [ 40 ]. Similarly, such a close molecular relatedness was also observed among 10 strains classified to SL2-ST2-CT4325, isolated mainly from RTE food and four strains (IDs: 27816, 27834, 27838, 27842) characterized by Kurpas et al [ 40 ] ( Figure 3 , Tables S1 and S3 ).…”
Section: Resultsmentioning
confidence: 91%
“…It was found that the current strains classified to clonal complex CC1 did not reveal any genotypic relationship with 59 strains of the corresponding CC, recovered from patients with listeriosis ( n = 38), food ( n = 19), and food production environments ( n = 2) in other countries. Comparison with 20 other L. monocytogenes strains previously isolated in Poland, including 14 isolates from clinical cases, showed that some of these, e.g., the current isolates of cgMLST type SL1-ST1-CT322 (IDs 47065, 47070, 47071, 47100, and 47122) and one strain previously described by Kurpas et al [ 40 ] (ID 27929) displayed a very close molecular relationship with up to 7 allelic differences, although they had been isolated in different regions of Poland and in different years. A similar genetic relationship was noted for L. monocytogenes ID 47098 and the previously isolated strain ID 27845, both classified to CT4326 and recovered from RTE food, which showed 7 allelic difference in the cgMLST analysis ( Figure 2 , Tables S1 and S3 ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In a previous study, we characterized L. monocytogenes from different turkey processing plants in the United States for their resistance to a panel of phages [ 12 ]. The majority of the phage-resistant strains were of serotype 1/2a, followed by 1/2b and 1/2c, i.e., serotypes which are commonly encountered in food and food processing ecosystems [ 12 , 28 , 29 , 30 , 31 ]. In the current study, our objective was to integrate whole genome sequence analysis, phage adsorption assays and phenotypic characterization of WTA decorations in order to elucidate mechanisms mediating phage resistance in FPE-derived serotype 1/2a strains.…”
Section: Introductionmentioning
confidence: 99%